2022
DOI: 10.1037/rev0000286
|View full text |Cite
|
Sign up to set email alerts
|

Automatic and controlled antecedents of suicidal ideation and action: A dual-process conceptualization of suicidality.

Abstract: Dual-process models of cognition distinguish relatively automatic from relatively controlled processes in terms of their interactive impact on perception, judgment, and behavior. Such models have advanced explanation and prediction in a variety of domains across psychology but have yet to be comprehensively applied to the pressing societal and public health problem of suicide. We propose a model of suicide that integrates dual-process models of social cognition with ideation-to-action conceptualizations of sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 220 publications
0
15
0
Order By: Relevance
“…As such, continued focus on assessing and reducing physical access to individuals’ potential suicide methods is warranted, though this should particularly be done in conjunction with other empirically supported interventions to manage suicidal crises (Barber & Miller, 2014; Betz et al, 2016; Bryan et al, 2017; Stanley & Brown, 2012). More broadly, interventions that increase one’s opportunity (i.e., time, cognitive capacity) to consider and enact behavioral alternatives in the context of low psychological distance to suicide methods may have particular utility (Olson et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, continued focus on assessing and reducing physical access to individuals’ potential suicide methods is warranted, though this should particularly be done in conjunction with other empirically supported interventions to manage suicidal crises (Barber & Miller, 2014; Betz et al, 2016; Bryan et al, 2017; Stanley & Brown, 2012). More broadly, interventions that increase one’s opportunity (i.e., time, cognitive capacity) to consider and enact behavioral alternatives in the context of low psychological distance to suicide methods may have particular utility (Olson et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…(Barber & Miller, 2014;Betz et al, 2016;Bryan et al, 2017;Stanley & Brown, 2012). More broadly, interventions that increase one's opportunity (i.e., time, cognitive capacity) to consider and enact behavioral alternatives in the context of low psychological distance to suicide methods may have particular utility (Olson et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Traditional dual‐process models distinguish the influence of automatic, non‐conscious processes from controlled, deliberative processes in attention (Posner & Snyder, 1975), memory (e.g., Linscott & Knight, 2001), and other domains of functioning. Olson et al (2021) have suggested that perceived belonging and burden, as well as other components within the interpersonal model, have automatic and controlled counterparts. Critically, these operate over distinct time‐frames and contribute independently to the emergence of suicidal thinking and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The first (B1), which predates this discussion and continued without being necessarily affected by it, was the branch of studies that use the duality as a framework to investigate specific behaviours. Recent examples include tolerance of minority groups (Verkuyten et al 2022), vaccine hesitancy (Bilewicz and Soral 2022) and suicidal ideation and action (Olson et al 2022), amongst many others. The second branch (B2) is the one in which Evans and Stanovich intervened more directly, which discusses dual-process theories per se.…”
Section: Introductionmentioning
confidence: 99%